OPTIMIZATION OF UNIQUAC INTERACTION PARAMETERS FOR ABSORPTION REFRIGERATION MACHINE WORKING FLUIDS. (Sciences & Technologie. B, Sciences de l'ingénieur, 2017)
To be able to pre-select new working fluids for absorption refrigeration systems, it is necessary to have a good understanding in the calculation or correlation of thermophysical properties of working fluids.  The choice of the most appropriate thermodynamic model for the prediction or calculation of thermodysical properties is a crucial task. Consequently the present study deals with the determination of excess properties for refrigerant mixtures which are required for the calculation of the various involved enthalpies and hence the used refrigeration machine. The present study considered the pairs (2-chloro-1,1,1,2-tétrafluoroethane) (R124) as a refrigerant in combination with an organic absorbent (N, N’- Dimethylacetamide) DMAC and  (1,1,1,2-tetrafluoroethane) (R134a) as a refrigerant in combination with an organic absorbent dimethylether tetraethyleneglycol (DMETEG) by calculating the molecular interaction parameters for the UNIQUAC model using the excess enthalpy of mixing at eight different temperatures varying from 0°C to 140°C by a step of 20°C for the first pair and varying from 20°C to 140°C for the second pair.The obtained interaction parameters values led to mixing excess enthalpy results very close to experimental values, contrary to the UNIFAC model which showed huge deviations. Therefore the optimization technique based on the Simplex method proved to be very reliable in the determination of interaction parameters for the UNIQUAC model.